The influence of family support in alleviating back pain among pregnant wome - Jasmiati Jasmiati; Nurmila Nurmila; Hendrika Wijaya Katrini Putri; Elizar Elizar; Nova Sumaini Prihatin; Rosyita Rosyita (Science Midwifery, 2025)
Massage therapy can be provided to alleviate back pain in pregnant women with the aim of enhancing physical relaxation, making it safe and without adverse effects on the mother or fetus. This therapy can be performed by anyone, including family members serving as birth companions. This study aimed to determine the effect of family accompaniment on skills in managing back pain. This research employed a quasi-experimental design with a one-group pretest–posttest approach. The sample consisted of 30 pregnant women at Banda Sakti Public Health Center. Data were analyzed using the paired t-test. The results showed that the mean pretest skill score was 30.83, which increased to 79.72 in the posttest, with a p-value of 0.000. The study concludes that family-based accompaniment has a significant effect on improving skills in managing back pain among pregnant women at Banda Sakti Public Health Center.